Pengaruh Profitabilitas (Return On Equity), Leverage (Debt to equity Ratio), Likuiditas (Current Ratio) terhadap Nilai Perusahaan (Price to Book Value) pada Sub Sektor Farmasi - Mala Anggrainie Putri; Purnamawati Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to examine the effect of Return On Equity, Debt to Equity Ratio, and Current Ratio in the pharmaceutical companies listed in the Indonesia stock exchange In the period 2017-2020 The method used is purposive sampling and obtained as many as 8 company. Technical analysis used multiple linier regression. The results of this study indicate that Return On Equity, Debt to Equity Ratio, and Current Ratio together have a significant effect on the price book value with an R Square of 60.9%. While individually, Return On Equity has a negative and insignificant effect on price book value, while Debt to Equity Ratio and Current Ratio have a positive and significant effect on price book value